Comparative analysis of means to control the thermal regime of a cooling thermoelement while minimizing the set of basic parameters - Zaykov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a comparative analysis of the thermal regime control means while minimizing a set of basic parameters in various combinations with the indicators of reliability and dynamics of the functioning of a single-stage thermoelectric cooler. The connection has been established between the optimal relative operating current corresponding to the minimum of the set on the relative temperature difference and heat sink capacity of the radiator. The results of calculating the main parameters, reliability indicators, time of entering the stationary mode of operation for various current modes of operation at a fixed temperature difference, thermal load at different geometry of the branches of thermoelements are given. A comparative analysis of the main parameters, indicators of the reliability and operational dynamics of a single-stage cooler under various characteristic current modes of operation has been carried out. Minimizing the set of basic parameters in conjunction with the reliability indicators and operational dynamics of the cooling thermoelement provides a decrease in the refrigeration coefficient up to 40 % compared to the maximum cooling capacity mode, as well as the optimal heat sink capacity of the radiator, the amount of energy expended, the time of entering the stationary mode, the relative intensity of failures. The analysis of the influence of the temperature difference at a predefined thermal load on the relative operating current, the time it takes for the cooler to enter the stationary thermal regime, the heat sink capacity of the radiator, the relative intensity of failures has been performed. The devised method of optimal control over the thermal regime of a single-stage thermoelectric cooler based on minimizing the set of basic parameters makes it possible to search for and select compromise solutions, taking into consideration the weight of each of the limiting factors